Microstructure and Optical Properties of SPION/Sr3V2O8:Er3+, Yb3+ Nanocomposites Synthesized by Microwave-Assisted Metathetic Method - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
The nanocomposites of Er3+/Yb3+ co-doped Sr3V2O8 (Sr3V2O8:Er3+/Yb3+) with superparamagnetic iron oxide nanoparticles (SPIONs) have been successfully synthesized by a microwave-assisted metasthetic method followed by heat-treatment. The microstructure exhibited well-defined and homogeneous morphology with the Sr3V2O8:Er3+/Yb3+ particle size of 1-2 μm and Fe3O4 particle size of 100-500 nm. The Fe3O4 nonoparticles were self-preferentially crystallized and immobilized on the surface of Sr3V2O8:Er3+/Yb3+ particles. The synthesized SPION/Sr3V2O8:Er3+/Yb3+ nanocomposites were characterized by X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Other optical properties were also examined using photoluminescence emission measurements and Raman spectroscopy.